Diversity of Epiphytic Ferns in the Girimanik Natural Forest Area (NFA), Wonogiri Regency, Central Java - Anggraeni, Saraswati; Santhyami, Santhyami (Jurnal Biologi Tropis, 2025)
The Girimanik Natural Forest Area (NFA) dominated by that has the potential to harbor high biodiversity, but research on this potential is still limited, especially on low-level plants such as epiphytic ferns. This study aims to ascertain the existence and variety of epiphytic ferns in the Girimanik Natural Forest Area (NFA). The data collection strategy employed was an exploratory approach utilizing the Systematic Line Sampling technique. The assessment of fern diversity in the Girimanik Natural Forest Area (NFA) revealed the presence of 18 species across 7 families: Lomariopsidaceae, Aspleniaceae, Polypodiaceae, Davalliaceae, Dryopteridaceae, Hymenophyllaceae, and Nephrolepidaceae. Epiphytic ferns inhabit the surfaces of host trees (phorophytes) and are characterized by rough and aged bark. Davallia denticulata and Davallia solida dominate the distribution of individual epiphytic ferns. Among the 18 species, two epiphytic ferns, Dryopteris arguta and Elaphoglossum blumeanum, are endangered, necessitating intensified conservation efforts to avert extinction. The findings of this study may serve as recommendations for stakeholders involved in conservation initiatives for epiphytic fern species, particularly those that are threatened.